THE INFLUENCE OF THE APRON MOVEMENT CONTROL (AMC) UNIT SURVEILLANCE ON AIRSIDE SAFETY AT TJILIK RIWUT PALANGKA RAYA AIRPORT - Marella Regina, Kezia Devina; Rochmawati, Laila; Rozi, Fahrur (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2024)
The monitoring of order and safety in the apron area of Tjilik Riwut Airport in Palangka Raya, which is the responsibility of the Apron Movement Control (AMC) unit, has become increasingly critical as the number of flights rises, leading to a higher potential for accidents and incidents. This descriptive quantitative research employed observation and questionnaires, using simple linear regression analysis and t-tests to test the hypothesis, along with Likert scale techniques for data analysis. The findings indicate that the oversight carried out by AMC personnel has a strong and significant correlation with airside safety, with a correlation coefficient of 0.780, suggesting that enhancing supervision by AMC and Airside Operators will significantly contribute to improving safety on the airside.